2017
DOI: 10.3390/nu9060567
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Mixture of Choline Forms to Lactating Dams Improves the Development of the Immune System in Sprague-Dawley Rat Offspring

Abstract: Dietary choline is essential during lactation, but few studies have examined the implications of feeding a mixture of choline forms on immune function. This study investigates the impact of feeding lactating dams different mixtures of choline forms, similar to those in human diets, on the development and later immune function of suckled offspring. Sprague-Dawley lactating dams (n = 6/diet) were randomized to consume one of three diets, containing 1 g/kg choline: Control (100% free choline (FC)), Mixed Choline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The same laboratory found that pups from dams fed a mixture of choline products (glycerophosphocholine, phosphatidylcholine, and free choline) gained more weight and their Con A-challenged splenocytes had greater proportions of helper T cells but produced fewer IFN-ɤ and TNF-α compared with pups from dams fed only free choline ( 55 ). These results imply that choline products and quantity fed modulate inflammatory response differently, potentially mediated by the activity of the enzymes involved in their synthesis and/or hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The same laboratory found that pups from dams fed a mixture of choline products (glycerophosphocholine, phosphatidylcholine, and free choline) gained more weight and their Con A-challenged splenocytes had greater proportions of helper T cells but produced fewer IFN-ɤ and TNF-α compared with pups from dams fed only free choline ( 55 ). These results imply that choline products and quantity fed modulate inflammatory response differently, potentially mediated by the activity of the enzymes involved in their synthesis and/or hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been suggested that the form in which dietary choline is consumed should be considered [ 11 ]. Evidence from animal studies have shown that different forms of choline present in milk will be utilized differently, as evidenced by the fact that maternal and offspring immune systems respond differently to various forms of choline consumed [ 12 , 13 , 14 , 15 ]. Therefore, the intake of different forms of choline should be considered relevant at specific stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphocholine is an intermediate in the CDP-choline pathway, formed when free choline is phosphorylated via enzyme choline kinase; therefore, the reduction in the proportion of phosphocholine is likely attributed to the decrease in precursor, FC. Richard et al (2017) has further described the effects of altering the forms of choline in the maternal diet on offspring stomach content [ 18 ]. At this time, the potential consequences of altering the forms of choline in the offspring’s diet, such as reducing the proportion of choline from phosphocholine, are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, consistent with our observations, Tokes et al, (2015) reported in vivo that administration of GPC attenuated intestinal superoxide production after ischaemia-reperfusion injury, suggesting a possible anti-inflammatory role of GPC [ 41 ]. Our study in lactating dams and offspring [ 18 ] was the first to specifically look, in an experimental model, of providing GPC, a major choline metabolite found in dairy foods (particularly milk), in the diet. As a supply of GPC appears to be important, future studies should be designed to elucidate the immunomodulatory actions and mechanisms of different proportions of GPC in mixtures containing the other choline containing molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation